Differential expression of the five redox complexes in the retinal mitochondria or rod outer segment disks is consistent with their different functionality. Issue 5 (31st March 2020) - Bruschi, Maurizio; Bartolucci, Martina; Petretto, Andrea; Calzia, Daniela; Caicci, Federico; Manni, Lucia; Traverso, Carlo Enrico; Candiano, Giovanni; Panfoli, Isabella
Abstract: Purpose: The retinal rod outer segment (OS) disk membranes, devoid of mitochondria, conducts oxidative phosphorylation (OxPhos). This study aimed at identifying which proteins expressed in the retinal rod OS disks determined the considerable adenosine‐5'‐triphosphate production and oxygen consumption observed in comparison with retinal mitochondria. Procedures: Characterization was conducted by immunogold transmission electron microscopy on retinal sections. OxPhos was studied by oximetry and luminometry. The proteomes of OS disks and mitochondria purified from bovine retinas were studied by mass spectrometry. Statistical and bioinformatic analyses were conducted by univariate, multivariate, and machine learning methods. Results: Weighted gene coexpression network analysis identified two protein expression profile modules functionally associated with either retinal mitochondria or disk samples, in function of a strikingly different ability of each sample to utilized diverse substrate for F1 Fo ‐ATP synthase. The OS disk proteins correlated better than mitochondria with the tricarboxylic acids cycle and OxPhos proteins. Conclusions: The differential enrichment of the expression profile of the OxPhos proteins in the disks versus mitochondria suggests that these proteins may represent a true proteome component of the former, with different functionality. These findings may shed new light on the pathogenesis of rod‐driven retinal degenerative diseases.